2021
DOI: 10.1093/trstmh/trab024
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of adult respiratory infections in primary care clinics in Myanmar: understanding the burden of melioidosis, tuberculosis and other infections not covered by empirical treatment regimes

Abstract: Background Lower respiratory infections constitute a major disease burden worldwide. Treatment is usually empiric and targeted towards typical bacterial pathogens. Understanding the prevalence of pathogens not covered by empirical treatment is important to improve diagnostic and treatment algorithms. Methods A prospective observational study in peri-urban communities of Yangon, Myanmar was conducted between July 2018 and Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…The low proportion of included studies compared to the total initial studies could be a reflection of the well-defined inclusion criteria based on the WHO criteria of GBD. The inclusion of several highquality studies in the review, [13][14][15][16][17][20][21][22][23][24][25][26][27][28][29]30,[34][35][36][50][51][52][53][78][79][80][98][99][100][101][111][112][113]119 would mean that the outcome of this review can be relied upon to make policies on rehabilitation in the selected conditions, especially the neurological conditions. A major observation is the very few high-quality publication on diarrhoea and low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…The low proportion of included studies compared to the total initial studies could be a reflection of the well-defined inclusion criteria based on the WHO criteria of GBD. The inclusion of several highquality studies in the review, [13][14][15][16][17][20][21][22][23][24][25][26][27][28][29]30,[34][35][36][50][51][52][53][78][79][80][98][99][100][101][111][112][113]119 would mean that the outcome of this review can be relied upon to make policies on rehabilitation in the selected conditions, especially the neurological conditions. A major observation is the very few high-quality publication on diarrhoea and low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Melioidosis was first described in Myanmar in 1911, but it was not recognized as a continuing cause of sepsis in that country for decades until recently. A nationwide soil study has confirmed the widespread presence of B. pseudomallei in Myanmar [38], but a study from Yangon has shown that the burden of tuberculosis is far greater than that of melioidosis [39].…”
Section: Epidemiologymentioning
confidence: 99%
“…In a second investigation, another melioidosis case in the USA with no international travel history was linked by genotyping of environmental B. pseudomallei to infection from a freshwater home aquarium that had contained imported tropical fish [35 & ]. [38], but a study from Yangon has shown that the burden of tuberculosis is far greater than that of melioidosis [39].…”
Section: Americasmentioning
confidence: 99%
“…This study used a real-time PCR assay to detect the presence of specific viral pathogens, including influenza A virus, influenza B virus, and respiratory syncytial virus (RSV). The results showed that among the 299 participants, 5.2% were positive for influenza A virus, 6.6% were positive for influenza B virus, and 4.4% were positive for RSV [128].…”
Section: Etiological Causes Of Lrti In People With Presumptive Tbmentioning
confidence: 99%